In the coevolution of cotton and pathogenic fungi, resistant cotton varieties lead to an escalation in the virulence of Verticillium dahliae - Yalin Zhang; Lifang Cui; Ruibing Liu; Zili Feng; Hongjie Feng; Jinglong Zhou; Lihong Zhao; Feng Wei; Heqin Zhu (Ecotoxicology and Environmental Safety)
Verticillium dahliae is highly prone to pathogenic differentiation and influenced by host cotton's resistance. To better understand the mechanisms of this phenomenon, we applied the host selective pressures of resistant and susceptible cotton varieties on V. dahliae strain Vd076 within an artificial cotton Verticillium wilt nursery and greenhouse. Consequently, among the offspring strains, high virulence strains exhibited higher levels of physiological characteristics and genetic diversity compared to moderate and low virulence strains. Moreover, whole genome resequencing revealed that the Ka/Ks ratio of single nucleotide polymorphism (SNPs) in the majority of the offspring strains was about 0.6, indicating an adverse selection impact in the offspring strains. Pathogenicity assays demonstrated that the virulence of the offspring strains triggered by continuous induction of disease-resistant cotton cultivar increased from the 4th generation and reached its peak by the 6th generation. Additionally, the transcriptome analysis revealed that the 4th and 6th generations of strains differentially expressed genes (DEGs) accumulated a significant number of response genes associated with pathogen pathogenicity differentiation, including the mitogen-activated protein kinase (MAPK) signaling pathway, amino and antibiotic biosynthesis, phenylpropanoid metabolism. Furthermore, VDAG_04757, VDAG_06462, VDAG_03218, and VDAG_08487 genes exhibited significant correlation with the pathogenicity of V. dahliae. Collectively, this study has significant implications for elucidating the evolution of virulence in V. dahliae induced by the host, as well as for advancing holistic strategies for preventing and managing Verticillium wilt disease.